CONSTRUCTAL DESIGN OF AN ISOTHERMAL BODY AND A LID DRIVEN CAVITY FILLED WITH A METALLIC NANOFLUID - da Silveira Borahel, Rafael; Martta Rodrigues, Priscila; Schwarz Franceschini Zinani, Flávia; Oliveira Rocha, Luiz Alberto (Revista de Engenharia Térmica, 2025)
The present work aims to numerically evaluate and maximize, through the Construtal Design method and the exhaustive search, the convective heat transfer between an isothermal block (IB) and the surrounding flow in a lid-driven cavity. As working fluid, a metallic nanofluid (water + Al2O3) – with different concentrations of Al2O3 particles (ψ = 0, 1, 2 and 3%) – is used. The degrees of freedom admitted for the system are the IB and cavity aspect ratios, while their areas are the constraints. Altogether, 36 different configurations were tested for the problem, resulting in an equal number of numerical simulations solved in the commercial software ANSYS Fluent 2022 R2. Based on the obtained results, it was observed that the convective heat transfer was intensified when the cavity assumed a horizontally elongated shape, with the isothermal block having a tall configuration. Regarding the effects of nanoparticle concentration, it was observed that a higher concentration contributes to improve the convective heat transfer within the cavity. This can be attributed to the modifications that arise in flow properties, particularly in the thermal conductivity, by the addition of nanoparticles to the base fluid.